Accuracy of alternative indexes for assessing the nutritional status of men and women - Guilherme Adroaldo Moraes Pereira; Silvana Corrêa Matheus; Diego Rodrigo Both; Mauri Schwanck Behenck (Universidade Federal de Santa Catarina, 2017)
A good evaluation of the nutritional status requires knowledge on body composition, casting doubts on the accuracy of some indexes. herefore, the aim of this study was to analyze the accuracy of the following nutritional status indexes: Body Mass Index (BMI), BMI elevated to 2.5 (BMI2.5), Fat Mass Index (FMI) and BMI adjusted for fat mass (BMIfat). Participated of this study 280 subjects (aged 17-48 years), from which the results of BMI, BMI2.5, FMI and BMIfat indexes were analyzed, having the Hydrostatic Weighing method as reference. FMI presented the highest concordance value, but classiied as discrete (k=0.21). he other indexes presented small concordance with results of the reference method (k<0.20). In conclusion, none of the indexes investigated has good accuracy in assessing the nutritional status of the study group, considering that, although they show results of correlation with the reference method, they do not reach the minimum agreement criterion.